Peroral poisoning leading to lung complications - Tutanc, Murat; Karcioglu, Murat; Kocamaz, Halil; Gunes, Ali; Ozel, Abdlkadir; Bosnak, Mehmet; Haspolat, Kenan (Dr Behcet Uz Cocuk Hastaliklari ve Cerrahisi, 2012)
Objective: Hydrocarbon compounds swallowed orally show their effects with tissue hypoxia, pulmonary irritation, and systemic toxicities. Pulmonary damage leads to various complications leading to death. In this study, cases of poisoning with paint thinner, turpentine, and kenaz were reported to call attention to the subject. Methods: Information related to the patients were gathered, retrospectively. Effects of inhaled corticosteroids for pulmonary complications were evaluated. Results were discussed in the light of the literature. Results: Twelve of them presented with pulmonary rales, six patients manifested severe respiratory distress, five patients had leukocytosis, and five patients fever. Besides three patients were unconscious, and two patients had impaired liver function tests. Interestingly, respiratory symptoms became prominent after a period of 24 hours in five patients. All patients were discharged within a period of 3 to 8 days after medical treatment. Conclusion: We used inhaled corticosteroids for the treatment of pulmonary complications, but further studies are required to certainly assert their beneficial effects in this field. Most of such type of poisoning can be avoided. On the other hand, parents should be aware of such dangers.
Keywords: Children; poisoning; pulmonary complications; inhaled budesonide